Search strategies and the value of a large collection - Gollin, Douglas; Smale, Melinda; Skovmand, Bent (International Food Policy Research Institute, 2003)
While the agricultural productivity benefits of utilizing new germplasm have been widely documented (Evenson 2001; Alston, Norton, and Pardey 1998), some controversy remains about the economic justification for expanding existing collections of crop genetic resources. Concerns persist that germplasm collections are underutilized (Wright 1997) and there-fore of questionable economic value. Does infrequent “use” of genebanks in crop breeding programs imply that accessions in genebanks have little economic value? Are seed banks really “seed morgues”?